Risk Identification in Residential Construction Project: A Systematic Literature Review - Daniel Kurniawan Sunarjo; Priyawan Priyawan (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
Risk is always present in every construction project. Residential building construction projects have various risks and are likely to be affected due to their difficulty and multiple operations and threats. Purpose of this journal is to understanding risk factors in a residential construction project spread over several countries, with various project size and complexity, and to get up to date research information. Risk factors are divided into three categories, namely internal factors, projects, and external factors. Three categories above is further divided into two technical and non-technical risk. This journal review 40 selected journals that discuss risk identification and risk management in residential construction projects. Risk factors in residential projects are generally very diverse and give us an idea that the interrelationships between the parties with an interest in the project contribute to the risk factors themselves occurring in the course of the project. It has been mentioned that the risk factors that occur in residential projects are something that is commonplace in various countries, in this case contributing to the success of the project. Outline on this journal has succeeded in providing information on the extent to which risk factors are currently occurring and there is a high potential for a change in the percentage of risk factors according to the classifications presented in this journal for other construction projects in the future.